PENGETAHUAN DAN SIKAP MASYARAKAT TERHADAP SISTEM PERTANIAN SONOR DI DESA SECONDONG KECAMATAN PAMPANGAN KABUPATEN OGAN KOMERING ILIR PROVINSI SUMATERA SELATAN - Yuli Rosianty; Delfy Lensari; Riko Riko (Tengkawang : Jurnal Ilmu Kehutanan, 2022)
The Sonor farming system is an agricultural system that clears land by burning, which is a tradision arried out by the people of Secondong Village. The Sonor system is one of the couses of land fires in South Sumatra. This study aims to analyze community community knowledge of sonor farming systems, analyze the factors that influence people's knowledge of sonor farming and community attitudes that can be done to prevent sonor farming. The research was conducted in Secondong Village, Pampangan District, OKI Regency, South Sumatra Province in August 2019. Using a survey method with descriptive qualitative data analysis and a Likert Scale test. The results showed that 77% of the people of Secondong Village carried out land burning, the people of Scondong Village had quite high knowledge about sonor farming systems which were considered an effective and efficient and cost-effective method. There are two factors that affect the public's interest in burning land, namely the lack of public understanding of the impacts of land burning (75%) and habits that have been passed down from generation to generation (73%), the absence of counseling so that there is no land clearing in other ways. Communities have good potential to prevent sonor farming systems (82%) if supported by extension activities and environmentally friendly technologies for clearing agricultural land.